Tensiomyography in physical rehabilitation of high level athletes - Dias, P. S.; Fort, J. S.; Marinho, D. A.; Santos, A.; Marques, M. C. (The Open Sports Sciences Journal, 2010)
The proprieties of a skeletal muscle were examined using the method Tensiomyography (TMG) in team sports high-level athletes who contracted a skeletal muscle injury, lesion confirmed by a magnetic resonance image (MRI). The analysis by the TMG is performed during the rehabilitation process, a non-invasive method, allowing the recording of chances in muscle following parameters: Td (time of reaction); Tc (time of contraction); Dm (maximum displacement); Tr (time of relaxation) and Ts (time of during contraction). Therefore, the aim of the study is to analyze the muscular reaction to the process of rehabilitation training.